Quand l’habit fait l’artiste : du peintre en bâtiment au peintre décorateur ou les identités multiples d’une profession (fin XIXe-début XXe siècle) - Claire Le Thomas (Images du Travail, Travail des Images)
House painter, decorative painter, director of a painting enterprise, all these professionals paint the interior and exterior of buildings and execute the ornament (false marble, false wood, friezes, cartridges, sign and letter) on shop windows and in stores, cafes or inhabitations. Thus, these different names show an internal sociocultural hierarchy that has identity implications. Moreover, with the arrival of young painter pursuing artistic ambitions, the career’s mental image, usually associated with crafts and working-class groups, transform itself. Which characteristics define these different identity building and to what extend do they appear in clothing? Analysing a large range of archive (photographs, professional handbook and magazines, iconographic volumes and plates, death inventory or bankruptcy files), this paper explore the house painter multiple identity and how they appear in clothing accessories during the end of the nineteenth and the beginning of the twentieth centuries.